The penalty. Their presence as punitive damages in civil law - López Soria, Yudith (2021)
The issue of punishment in civil law is for countries that follow a Roman-Germanic model, a bit rare, the law has advanced in this region leaving the issue of punishment exclusively to sanctioning law, and that is not exactly the conception within Civil Law, also Romano-Germanic. In this way and before the observation caused by a deep bibliographic review, this article is proposed that aims to: Learn about the criminal-legal Institution of Punitive Damages present in Anglo-Saxon civil law and demonstrate its influence on European and Latin American law. To reach this result, research methods have been used, such as bibliographic review, documentary analysis, historical-logical and inductive-deductive, all of which lead to confirm the presence of punitive damages as a legal institution of Roman civil law. Germanic.